(untitled) (Papeles, 2009)
The present article wonders for the dilemma of the second half of the 20th century for the Latin-American writer, and for it, recaptures an emblematic writer, Pablo Neruda. Especially, it approaches the question of the compromised art, a symbolic category for the analysis of Neruda’s work. Finally, this paper proposes an analysis on the difference between the modern European poetry and Neruda’s poetical proposal in Latin America.